Pelatihan Pengembangan Pembelajaran Berorientasi Higher Order Thinking Skills (HOTS) Bagi Guru Sekolah Dasar - Antonius Alam Wicaksono; Nathasa Pramudita Irianti (Jurnal Pengabdian Masyarakat (abdira), 2022)
This activity aims to improve the skills development of elementary school teachers. HOTS based training. This event will be held in the form of an online workshop for two people. Activities, theory and practice sections. Delivery-Understanding the Importance of Developing HOTS for students to improve the quality of learning in schools Basic learning preparation strategies centered on HOTS according to learning methods HOTS and HOTS based learning assessments. Practice by composing. HOTS-centered learning based on the basic talents of every elementary school student. As a result, most of the participants were able to develop HOTS-based learning. Based on the results of product research One of the skills that need to be improved by the participants is skill development. productive question The method used is presentation and discussion which results in 19 teachers being able to apply the six competency skills in designing HOTS-based learning.